PERANCANGAN WEBSITE MARKETPLACE BERBASIS PHP DENGAN FRAMEWORK CODEIGNITER - Femmy Novica Ramadanis; Mohamad Daffa Adriansyah; Muhammad Fadhil Alamsyah; Rizkia Meinita; Tri Putra Satriawan; Ricky Firmansyah (Pusat Riset dan Inovasi Nasional, 2022)
The development of marketplace-based online trading facilities has been widely circulated in Indonesia. However, there are no services to provide marketplace-based jobs. Even though this service is really needed by the community, especially with the increasing number of unemployed in Indonesia. These employment services are website-based so that people don't have to go to each company, just stay at home and attach several files as support to get a job. With this application, information on job vacancies in an area can be disseminated on this system. This freelance marketplace distribution system was built using the waterfall method with four stages of applicable methods, namely requirements analysis, system design, implementation, and system testing using the PHP and Condigniter 3 programming languages. , ordering, talent details, logout.. On the other hand, the advantages of looking for a job online are that apart from being flexible, it can also open up new and broad opportunities. And it can reach various aspects of society.